Expression and quantity dynamics of CK5+-immunopositive thymic epithelial cells of the subcapsular zone in rats of the early postnatal period after prenatal introduction of staphylococcal anatoxin. - Voloshin, N. A.; Kushch, O. G.; Aravitskiy, E. O. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Epithelioreticulocytes form the cellular basis of microenvironment in thymus, which regulate the processes of proliferation and differentiation of T-lymphocyte progenitor cells. In the cytoplasm of the epithelial cells cytokeratin-intermediate filaments are synthesized, who affect the mechanical stability and integrity of the epithelium. The influence of staphylococcal anatoxin on the morpho-functional state of the thymus, and particularly on the morphology and receptor composition of the thymic epithelial cells, is ambiguous and requires a more detailed study. Objective. to study the peculiarities of the distribution and expression of cytokeratin 5 by the epithelial cells of the thymus in norm and after prenatal introduction of staphylococcal anatoxin. Methods. The study was conducted on 144 white non-linear rats at 1, 2, 3, 5, 9, 14, 21, 30 days after birth. There were 3 groups of 48 rats: group 1 - intact; group 2 - experimental, who were intrauterine and intrafetally injected with 0,05 ml of staphylococcal anatoxin (1:10) on the 18th day of pregnancy; group 3 - controls, that were injected 0,05 ml of 0.9% NaCl. The standard sets of monoclonal mice antibody produced by Sigma-Aldrich (St. Louis, USA), and visualization system produced by Santa Cruz Biotechnology (California, USA) were used to study the receptor distribution to cytokeratin 5. Results. During the 30 days after birth in a group of rats, who had been introduced staphylococcal antigen, an increase in CK5 receptors expression was detected, with a peak within first three days and on the 14th day of life. The area occupied by CK5+-epithelioreticulocytes is significantly more than 1.5 times in rats of the experimental group from the 1st to the 9th day after birth, with a maximum on 1 day (29865 ± 3623 pix), decreasing further and almost reaching values of intact and control groups of rats up to the 30th day of observation. Conclusion. The revealed changes indicate a higher functional activity of epithelioreticulocytes, as microenvironmental cells, and their influence on the positive selection processes in the early postnatal period of ontogenesis in rats of the experimental group.